2017
DOI: 10.1002/ange.201707346
|View full text |Cite
|
Sign up to set email alerts
|

A Smart Metal–Organic Framework Nanomaterial for Lung Targeting

Abstract: Despite high morbidity and mortality associated with lung diseases,a ddressing drugs towards lung tissue remains ap ending task. Particle lung filtration has been proposed for passive lung targeting and drug delivery.H owever,toxicity issues derived from the long-term presence of the particles must be overcome.Byexploiting some of the ignored properties of nanosized metal-organic frameworks it is possible to achieve impressive antitumoral effects on experimental lung tumors,e ven without the need to engineer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Previously, a type of nano MOF was reported to target lung tissues based on its pH-responsiveness and reversible aggregation behavior. [52] The report describes that after intravenous administration into neutral-pH blood, MIL MOF nanoparticles formed microsized particles that were retained within lung capillaries. Subsequently, owing to its charged species and protein adsorption on the surface, the aggregated MOFs progressively disaggregated to restitute the initial MOF nanoparticles.…”
Section: Rcld Nanoparticles Target Lung Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a type of nano MOF was reported to target lung tissues based on its pH-responsiveness and reversible aggregation behavior. [52] The report describes that after intravenous administration into neutral-pH blood, MIL MOF nanoparticles formed microsized particles that were retained within lung capillaries. Subsequently, owing to its charged species and protein adsorption on the surface, the aggregated MOFs progressively disaggregated to restitute the initial MOF nanoparticles.…”
Section: Rcld Nanoparticles Target Lung Tumorsmentioning
confidence: 99%
“…Subsequently, owing to its charged species and protein adsorption on the surface, the aggregated MOFs progressively disaggregated to restitute the initial MOF nanoparticles. [52] The CDF carrier was prepared by crosslinking nanoscale CD-MOF, and our preliminary research found that the hydrodynamic diameter and zeta potential of our CDF carrier were pH dependent, with acidic pH increasing particle diffusion and negative surface charge ( Figure S11, Supporting Information). Conversely, neutral and alkaline pH increased the hydrodynamic diameter and reduced the zeta potential of the carrier, leading to particle aggregation.…”
Section: Rcld Nanoparticles Target Lung Tumorsmentioning
confidence: 99%
“…Among the MOF family, nanosized MOFs (nanoMOFs) based on porous iron(III) polycarboxylates have emerged as an important class of biodegradable and non-toxic [4,5] materials that can be loaded with exceptional quantities (within the 20-70 wt% range) of a large variety of therapeutic agents [4,6]. This paved the way to novel perspectives in terms of targeted delivery of drugs [7,8] and theranostics [4]. For biomedical applications, it is of utmost importance to engineer the surface of the nanoMOFs, since the in vivo fate of any nanoparticle in the living body (biodistribution, pharmacokinetics and targeting abilities) depends upon its surface physicochemical properties.…”
Section: Introductionmentioning
confidence: 99%
“…This exponential growth has been underpinned, to some extent, on the thorough quest of rational design strategies to build/functionalize -in a controlled manner -MOFs with predetermined dimensionalities and topologies, [11][12][13] and the possibility to use X-ray crystallography to follow and rationalize the proposed synthetic methodology. [14][15][16] These have enable MOFs to find applications in such diverse fields as gas adsorption and separation, [17][18][19][20] catalysis, 21,22 molecular recognition processes, 23,24 drug delivery, 25,26 magnetism 27,28 and water remediation. [29][30][31] However, this has not been the case for MOFs constructed from one-dimensional (1D) rod-like Secondary Building Units (SBUs).…”
mentioning
confidence: 99%